COMPARATIVE STUDY OF THE GOOD FAITH CONCEPT BETWEEN INDONESIA AND THE NETHERLANDS IN CIVIL LAW - Miarsa, Fajar Rachmad Dwi; Saifudin, Muhamad; Santoso, Hardi Anugrah; Qoilun, Nur; Japar, Sugiarto Raharjo (YURIS: Journal of Court and Justice, 2024)
Indonesian law is not only dominated by the customary system, but also by the European legal system. Indonesia still adhered to the old Dutch “Burgelijk Wetboek” for several years after its independence, even though the Dutch had completely reformed their Burgelijk Wetboek with a more modern version. One of the significant changes that the Dutch implemented is the paradigm change in the regulation of good faith. Therefore, this research is conducted to determine the effect of paradigm changes in good faith under Dutch civil law on the design of legal arrangements in Indonesian civil law. The research method used is normative juridical which focuses on the problem analysis by approaching the principles and legal norms in the applicable laws and regulations, through statutory, comparative, and historical approaches. Good faith concepts in Indonesia and the Netherlands are basically contained in one specific article. The distinction between Indonesia and the Netherlands is the concept of good faith, which is only contained in the article and after the amendment of the new Civil Code in the Netherlands, it is contained in the heading of that article which stipulates that good faith must be applied.